Schoolchildren’s self-reported explanations of suicidal ideation - Žemaitienė, Nida; Zaborskis, Apolinaras (Psichologija, 2004)
This article presents nationally representative data on the prevalence of suicidal tendencies and self reported explanations of their causes. The analysis is based on the data of the survey conducted in 2002 according to the methodology of the WHO Cross-National study on Health Behaviour in School-aged Children (HBSC). The sample was expected to represent the whole country from the point of view of age, sex, nationality and the place of living. A stratified cluster sampling design was used to draw a sample of 11, 13 and 15 year old Lithuanian schoolchildren. Regarding the actual number of pupils in the lists of selected classes the response rate was approximately 96 percents. The final population of the cleaned data consisted of 5645 schoolchildren: 2887 (51.1%) boys and 2758 (48.9%) girls. The survey instrument was a standardized anonymous questionnaire. The focus question group concerning suicides was included into Lithuanian questionnaire version in order to study the suicidal ideation and behaviour in adolescents. The assessment of the prevalence of suicidal tendencies among schoolchildren was made considering answers to the question “Have you ever had any thoughts about suicide?” Reasons for suicidal thoughts or behaviour were reported in free form, replying to the question “If you have been at the edge to suicide (have had frequent thoughts, planned) or tried to commit it, give briefly the main reasons that have evoked such feelings or behaviour.” The findings demonstrated that suicidal tendencies are typical to about one third (32.5%) of eleven, thirteen and fifteen year old schoolchildren: 24.1% of respondents appointed that they sometimes have thoughts about suicide, 4.0% claimed to have frequent thoughts about it, 2.7% had thought about suicide rather seriously and making concrete plans how to commit it, 1.7% mentioned that they had tried to commit suicide. Girls tended to have suicidal inclinations almost twice more often than boys. The data received show, that schoolchildren were inclined to disclose triggers of their suicidal intentions. Various explanations of the reasons of suicidal tendencies were set forth by 42.7% of suicidal boys and girls. Discussing reasons for suicidal inducements, schoolchildren most often mentioned depressing feelings and experiences. Usually in the provided explanations there was no thorough description of situation or events; schoolchildren tried to define the way they feel in general terms, mentioning “tired” life, fatigue, loneliness, unhappiness, anger or desire of revenge. There is a great probability that beneath such expressions there could be hidden not only painful experiences caused by traumatizing events but also depression. Comparison by gender showed that girls were especially prone to refer to emotional, sensual experience, whereas boys more often gave concrete facts and events. Rather often while explaining reasons of suicidal attempts younger children named a wish to try one or other way of suicide, to experience “what a person feels when dying”, “what is life like beyond.” The carried out survey proved that such thoughts expressed by schoolchildren should warn about possible risk to a child who may be either eager to satisfy curiosity or not able to cope with emotional problems or misfortunes. These findings indicate that all signs of depressive mood and suicidal behaviour of adolescents must be taken seriously.